Pharmacokinetics of different selenium supplements in healthy individuals and patients with autoimmune thyroiditis after oral administration - Pece Sherovski; Jane Bogdanov; Natasha Ristovska; Trajče Stafilov (Macedonian Journal of Chemistry and Chemical Engineering)
Selenium is essential for the function of key selenoproteins such as glutathione peroxidase, thiore-doxin reductase, and iodothyronine deiodinase, which have antioxidant properties and support thyroid hormone metabolism. Due to the low selenium content in European soils – particularly in the Southeast-ern regions, supplementation is often recommended, especially for conditions like Hashimoto's thyroidi-tis. However, careful consideration of selenium dosage and pharmacokinetics is crucial, as the margin be-tween essential and toxic levels is very narrow. The aim of this study was to investigate the pharmacoki-netics of selenium absorption and plasma concentration following oral administration of various selenium doses and chemical forms, both in the short and long term, in healthy individuals and patients with auto-immune thyroiditis. Selenium concentrations in blood plasma were measured using electrothermal atomic absorption spectrometry (ETAAS). The study found that L-selenomethionine is absorbed more efficiently than inorganic sodium selenite, with peak plasma concentrations reached and sustained within 6 – 8 hours. Selenium levels remained elevated 48 hours after ingestion compared to baseline. At a daily dose of 200 μg of selenium as L-selenomethionine, plasma selenium concentrations increased by approximate-ly 30 %, and by about 25 % at 100 μg/day, relative to the initial value. Long-term studies showed that plasma selenium concentrations rose significantly after the first month of supplementation, with a slower increase in subsequent months. After supplementation ended, selenium levels declined rapidly. Interest-ingly, no significant differences in selenium absorption or excretion were observed between patients with Hashimoto's thyroiditis and healthy controls.